Tata Kelola Creating Shared Value (CSV) terhadap Peningkatan Kesejahteraan Masyarakat Kawasan Tambang - M, Nursafitra; Ramadani, Eka Fitra; Annas, Aswar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2022)
Based on the policies, policy directions and governance system for PT Vale's program implementation,has implemented the concept of Creating Shared Value (CSV), in three stages, namely The first stage; improvement of program quality and achievement targets, where at this stage PT Vale develops and improves product and packaging quality in order to enter a wider market, and open market access for manufactured products processed by program actors who already have standard quality. second stage; Productivity and value chain development, at this stage 5 superior products prepared to fulfill local marketing and Go Sulselbar, production achievement of 10,000 herbal drink cups, cultivated area up to 40 hectares to supply rice needs 3 tons/month organic for PT Vale employees, producing 15,000 fish products to fulfill the needs of fresh and healthy fish for Patra Catering and PT . employees Vale, Non-B3 (3R) waste management in partnership can create a value chain. Third phase; local cluster development through plan preparation and implementation program work, implementation of trainings for capacity building and institutions, support for the provision of facilities and infrastructure such as; fish pond for organic cultivation, making concrete boxes for fish apartments, supplying 3 units of combine harvester managed by BUMDESMA, and training on preparing vegetable farms organic.